SAT0681 DEVELOPMENT, ACCEPTABILITY AND USABILITY OF HIBOOT : A SMARTPHONE APP TO IMPROVE MEDICATION ADHERENCE, SAFETY AND SELF-ASSESSMENT IN PATIENTS WITH INFLAMMATORY ARTHRITIS. (June 2019) - Beauvais, Catherine; Pham, Thao; Montagu, Guillaume; Vidal, Celine; Dervin, Guillaume; Baudart, Pauline; Desouches, Sandra; Calvez, Julian Le; Lafarge, Delphine; Launois, Francoise Alliot; Carton, Laurence; Quatrebarbes, Marie De; et al.
Abstract : Background: There is an increasing interest for mobile health applications (Apps) to enhance patients self-management in rheumatology. However few have been developed involving patients and health professionals. Objectives: 1.To develop an App to improve medication adherence, safety and self-assessment in patients with inflammatory arthritis (IA) treated by biologics and/or methotrexate (MTX). 2. To assess its acceptability and usability. Methods: 4 steps. Step1. In 2016, a qualitative ethnographic study and a quantitative study including 21 and 344 patients respectively explored 1.the impact of IA in daily life, treatment practices, relationship between adherence and safety 2. the patients' use of health Apps in general, their needs in terms of content and potential use (refs). Step2. A multidisciplinary team including 7 rheumatologists, 3 patients association representatives and 4 members of a Digital company developed the first version of the App through face-to-face meetings and qualitative interviews of patients along the development process. The content was collectively reviewed to be understandable by the patients and general population. After the launching of the App (step3), the assessment (step4), consisted in a) a qualitative study including 7 patients with different profiles (current users or non-users, satisfied or not) and 3 rheumatologists, having or not counselled the App to their patients, and b) the number of loadings and current users. Results: Preliminary studies indicated numerous safety issues and needs on adherence and daily life counselling, leading the 5 mains functionalities of the App: a) a treatment reminder, b) a global well-being self-assessment c) a safety checklist before administration, d) help in daily life situations related to self-management and safety e.g. symptoms requiring to stop their treatment (infections, surgery) etc…e) periodic counselling messages. The presentation was a friendly companion called HIBOOT (OWL in English) that interacts with the user. The content was based on the French recommendations of the Club Rhumatismes Inflammation (www.cri-net.com) for biologics and MTX management, the drug leaflets and the public national health websites. In May 2017 : launching on the stores (GooglePlay and iTunes, with free uploading); May 2017- January 2018 : communication toward patients, rheumatologists and health professionals (flyers, postal letters, Facebook, Tweeter). Assessment showed 2 types of usability: a regular use by the patients who have adopted the HIBOOT companion and are in demand of more functionalities; a more punctual use on specific questions with the need of quick answers. The reminder system was particularly appreciated and the messages considered understandable and reliable. Patients suggested ways of improvement on the App navigation system and the check list. Rheumatologists appreciated the independent scientific content although having a low knowledge of the App. To date, the mean loading is ∼500/months with a regular use of ∼1500-1800 patients monthly. Conclusion: The free App HIBOOT for patients with IA was developed through a formal methodology using preliminary qualitative studies, inclusion of patients all along the process and has a scientific validated content. Its acceptability and usability is good and will be improved according to patient's advices. Communication is still necessary to enhance rheumatologist's adherence to promoting the App. Reference: [1] Montagu, et al. ARD, 2017; 76, suppl 2 (3) Beauvais, et al. ARD, 2017; 76, suppl 2 Acknowledgement: French Society of Rheumatology. Promotor French Society of Rheumatology. Institutional funding by Biogen, Nordic Pharma, Roche, Janssen, Novartis Disclosure of Interests: Catherine Beauvais: None declared, Thao Pham Speakers bureau: Lilly, Novartis, Guillaume Montagu Employee of: Unknowns strategic and innovation consulting, Celine Vidal: None declared, Guillaume Dervin : None declared, Pauline Baudart: None declared, Sandra Desouches: None declared, Julian Le Calvez Employee of: Unknowns strategic and innovation consulting, Delphine Lafarge Consultant for: Honoraria from Novartis for this project, Francoise Alliot Launois: None declared, Laurence Carton Grant/research support from: AMGEN UCB MYLAN BIOGARAN BIOGEN PFIZER LILLY GRUNENTHAL TEVA NOVARTIS JANSSEN EXPANSCIENCE SANOFI THUASNE MSD GENEVRIER ABBVIE, Marie De Quatrebarbes Employee of: Unknowns strategic and innovation consulting, Sonia Tropé: None declared, Henri Jeantet Shareholder of: strategic and innovation consulting, Jeremie Sellam: None declared